DAMPAK KEBERADAAN DERMAGA BATANG AJI TERHADAP KESEJAHTERAAN PENDUDUK DI KELURAHAN BAQA KECAMATAN SAMARINDA SEBERANG - Aisya Novia Rheinanda; Warsilan Warsilan; Andriawan Kustiawan (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
This Research aim to determine the influence of the Batang Aji Pier Area to surrounding people’s welfare measured through: recruitment of the workers and people income to determine how public attitudes about of the existence of the harbor. The analytical method used is by means of qualitative and descriptive analysis using primary data through interviews with 5 informants consisting of trading activities and services in the region. The analysis of the primary data shows that there is a significant increase in well-being and the existence of the Batang Aji Pier area. The result is concluded that the developing of Batang Aji Pier area has very significant impact to people’s welfare who live surrounding the area. It is reflected with increasing income through employing of many people supported by transportation factors